(Un)Seeing Goa’s Bom Jesus in Vishvesh Prabhakar Kandolkar’s This is Not the Basilica! - Ferrão, R. Benedito (Imaginations)

(untitled) (York University, 2023)
This article examines the interrogation of visual history associated with Goan church architectural legacies offered by Vishvesh Prabhakar Kandolkar’s installation series, This is Not the Basilica! (2021). The artist’s subject is the 16th-century Basilica of Bom Jesus, which was built in locally domesticated Baroque style during Goa’s Portuguese colonial era and which houses the remains of the Spanish saint, Francis Xavier. Kandolkar’s work makes viewers intimate with the Basilica’s history, I contend, so as to posit the need for conservation efforts that will save the deteriorating church while also revealing its unseen aesthetic past as a symbol of still-unfolding Goan identity.